OPTIMAL ROUTING INFORMATION FLOWS WITHIN THE PARAMETERS OF QOS - N. I. Listopad; I. O. Velichkevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
A classification of traffic in IP-based networks is described. The problem of traffic within the parameters of quality of service is formulated. The algorithms to maximize flow and minimize cost are reviewed. The algorithm of the problem of the «maximum minimum cost flow» is modificated so that would be taken into account when choosing a path not only cost, but also the delay. Implementation of this algorithm in Java is developed. The program to test the algorithm with the ability to model the characteristics of the network is written.